Fapemig and the ICT&I of Minas Gerais: What is the development project? (Research, Society and Development, 2023)
This article aims to present the development direction adopted by the Institutions of Science, Technology, and Innovation (ICT&I) in the state of Minas Gerais since the beginning of the 20th century. To address this perspective, we employed a qualitative, quantitative, and descriptive methodology, which was carried out through the study and analysis of the set of research projects approved by the Minas Gerais Research Funding Foundation (Fapemig) from 2008 to 2021. To fulfill this purpose, our investigation focused on gathering data about the scientific, technological, and innovative profile of a total of 24 ICT&Is in Minas Gerais: 11 federal universities in the state, 5 federal institutes, Cefet-MG, 2 state universities, PUC-Minas, Instituto Oswaldo Cruz, Unidade Instituto René Rachou (Fiocruz Minas), Brazilian Agricultural Research Corporation, Unidade Gado de Leite (Embrapa), Ezequiel Dias Foundation (Funed), and Agricultural Research Company of Minas Gerais (Epamig). These institutions are notably oriented towards advancing knowledge and are directly connected to cognitive processes historically involved in basic and applied sciences, aiming to deepen and expand knowledge about human beings, societies, nature, and cultures. This requires continuous financial investment from the state and dedication from the research community in the relentless pursuit of new learning and discoveries.